Manajemen Pembelajaran dalam Rangka Meningkatkan Prestasi Belajar - - Muhlasin (STAIN Bengkalis, 2019)
Management is a process to achieve a goal in the organization by carrying out activities from the main function, namely planning, organizing, leaders, and controlling. So that, the activities reaches the goals or objectives that have been set to develop the quality of the organization. Learning as an action in a planned and basic way, through a process of “action” (one-way communication between teachers and students), “interaction” (communication in many directions, namely between students and instructors, instructors and students, as well as students with participants other students) its resulting changes of behaviors. Learning management is a thought to carry out teaching tasks by applying the principles of learning, as well as through steps, which include planning, implementation, and evaluation in order to achieve education goals.